Kitab al-Aghdhiyyah of Abu Marwan 'Abd al-Malik ibn Zuhr (d. 1162) : an annotated translation - Medikawati, Mersita Eko (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2011)
This study is aimed to bring into existence the English translation of Kitab al-aghdiyyah, a work in medical science composed by Ibn Zuhr, an Andalusian physician who lived in the 11th century. The research is conducted based on literature study using books and manuscripts related to the topic as sources. The original text is an edited text published in Arabic by Institutode Cooperatión con el Mundo Árabe of Consejo Superior de Investigaciones Científicas, Spain. Kitab al-aghdiyyah has clearly shown how, in the Muslim world, medical science was dynamic rather than static by virtue of the physicians' passion for experimentation and observation. Through the discussion about food and their healing properties, Kitab al-aghdiyyah has made clear how important diet is in treating illnesses, employing a method called “dietotheraphy” that takes a relatively more holistic approach- as opposed to a reductionist one that modern medical science favours. As this book contains the author's findings never before discussed by any other physician or writer, it provides good evidence to refute the allegation that Islamic physicians were less than those from the Greek tradition. In tradition, it gives us a glance at the socio-cultural life in the Andalusian society in the 11th century. As the text contains references to many kinds of food, it provides us with information on the kinds of edibles available then. The author's description of several herbs that were not found in his country provides us clues on trading. More importantly, Ibn Zuhr's believe in God as the ultimate Healer, which is manifested in this book, ensures that Islamic medicine, based on an Islamic world view, is distinguished from other systems of medical science. Studies on the works of Muslim physicians, such as Ibn Zuhr's Kitab al-aghdiyyah, are necessary to construct the philosophy of Islamic medicine, besides filling the gap in the historical study of Muslim legacy. The availability of the English translation of these texts is expected to open avenues for others to conduct further research on the texts.